Elimination Of CVB (Chrysanthemum Virus B) From A Range Of ChrysanthemumTHE Varieties By Meristem Culture Following Antiviral and Heat Treatments - Kurniawan Budiarto; Budi Marwoto Budi; Lia Sanjaya Lia; Muchdar Soedarjo Muchdar; Indijarto Budi Rahardjo Indijarto (SEAMEO BIOTROP, 2011)
CVB elimination for retaining healthy protocols from infected chrysanthemum plant was investigated trough combined treatment of meristem culture with synthetic antiviral ribavirin and thermotherapy under in vitro conditions. The biological material used on the experimentation was constituted of six commercial varieties: Dewi Sartika, Saraswati, Yellow Fiji, White Puma, Yellow Puma and White Reagent. Tissue culture initiation was conducted through plantlet establishment using MS supplemented with IAA. Ribavirin was added in media treatments with the concentration of 40 mg/l. Parallel with this step, heat treatment with different durations (1, 2, and 3 weeks) was also conducted on the plantlets. Meristem culture was done following the chemo- and thermotherapy. The experiment resumed the failure single treatment of meristem culture in eliminating CVB from the infected chrysanthemum plantlets. Under heat treatment, percentage of virus-free plantlets increased along with the duration of thermotherapy, though the survival rate of plantlets decreased in lengthened heat treatment. The best results regarding virus free plant percentage was obtained when meristem culture was applied following ribavirin or three weeks heat treatment which effectively eliminated virus particles from the plant.